Plato's Timaeus : Proceedings of the Tenth Symposium Platonicum Pragense - Jorgenson, Chad,; Karfík, Filip,; Špinka, Štěpán, (Brill's Plato Studies Series ;, 2020)
Plato's 'Timaeus' brings together a number of studies from both leading Plato specialists and up-and-coming researchers from across Europe. The contributions cover a wide variety of topics, ranging from the literary form of the work to the ontology of sense perception and the status of medicine in Timaeus' account. Although informed by a commitment to methodological diversity, the collection as a whole forms an organic unity, opening fresh perspectives on widely read passages, while shedding new light on less frequently discussed topics. The volume thus provides a valuable resource for students and researchers at all levels, whether their interest bears on the Timaeus as a whole or on a particular passage.